Lo insólito en la novela Don Juan de Gonzalo Torrente Ballester : un nuevo concepto del mítico personaje y su lucha por la libertad - Mańkowska, Joanna (Acta Hispanica, 2015)
Torrente Ballester in his 1963 book offers a novel reading of the myth by presenting Tenorio, who is denied both the chance to repent himself and the punishment of the Inferno. For more than three centuries, accompanied by Leporello, who reveals himself as a devil incarnate, travels the World making friends with artists who devote him their works, without understanding his tragedy, however. In Paris of the mid-twentieth century he emerges as working on the plays on Don Juan by independent theatres and visits places attended by young and passionate followers of Sartre. At times his soul leaves his winsome body, to which he is destined for eternity, and possesses a Spanish intellectual, with an aim of writing down the true history of Tenorio clarifying his conflict with God, a conflict in which the freedom to decide on one’s fate is one of the fundamental issues. He challenges Him by defending his right to be condemned for a life in sin. God proves indifferent to his desperate blasphemies and Don Juan is faced with the recognition of human condition as unable to satisfy desires and being one’s genuine inferno.